Consumo de ceftriaxona en el servicio de geriatría del hospital nacional almanzor aguinaga asenjo – essalud- chiclayo, durante el año 2008” - Asmat Rubio, Martha Genara (2009)
This study had as objective to determinate the consumption of Ceftriaxone in service at Geriatrics of National the Hospital Almanzor Aguinaga Asenjo – EsSalud – Chiclayo, in 2008. It was made a descriptive-retrospective study expressing the consume in DDD/100 beds/day Defined Daily Dose. The trend of consumption through a correlation analysis and the corresponding test of statistical significance, units consumed, diagnostic classification, bacterial resistance and cost on new soles. The consumption of Ceftriaxone expressed in DDD/100 bed-days was 52,44 %. Trend tends to variability over time, being not p 0.05 statistically significant. The monthly consumption in units consumed was 2 905. The annual cost of this drug reached S/.19 277,5, representing 0.42% of total antibacterial treated at the Geriatric Department